Perancangan Pemanas dan Pengontrol Suhu Sesuai Kondisi Pada Mulut Manusia Berbasis Mikrokontroler Arduino Uno - Masfufiah, Ilmiatul (Jurnal IPTEK, 2019)
The design of heaters and temperature controllers based on Arduino uno were successfully overlaid as candidate temperature controllers. The heater made from nickel winding with a diameter of 0.25 with a wire length of 5 m by utilizing eddy current as an induction heater. The temperature controller used is the LM35 temperature sensor circuit, power supply, and Arduino uno microcontroller, which is connected to serial communication so that the value can be displayed on a PC. The data generated in the study are voltage calibration data on temperature, heating, sensor performance data and delay (delay time). The percentage of sensor performance in this study was 99.76%, with a delay of 0.802 ± 0.006. Based on the results of the performance and design data analysis, it can be concluded that the Arduino uno-based heater design and temperature controller can be applied as a temperature controller as a candidate for temperature detection according to mouth conditions in humans.